Math, asked by madan9881, 1 year ago

cosecA- cotA= underroot 1- cosA/ underroot 1+ cosA

Answers

Answered by sidhantsivakumar
0

Answer:

Step-by-step explanation:

Answered by meet76765
0

Answer:

Step-by-step explanation:

Taking RHS

√1-cosa/1+cosa

Multiply by 1-cosa/1-cosa

√1-cosa/1+cosa ×1-cosa/1-cosa

In denominator using identity (a+b)(a-b) and in numerator (1-cosa)^2

So √1-cosa)^2/1-cos^2a

1-cos^2a=sin^2a

So √(1-cosa)^2/sin^2a

1-cosa/Sina =1/sina-cosa/Sina

Coseca-cota

RHS=lhs

Similar questions